Aggregate Constraints for Virtual Manipulation with Soft Fingers - Talvas, Anthony (IEEE transactions on visualization and computer graphics, 2015)
Interactive dexterous manipulation of virtual objects remains a complex challenge that requires both appropriate hand models and accurate physically-based simulation of interactions. In this paper, we propose an approach based on novel aggregate constraints for simulating dexterous grasping using soft fingers. Our approach aims at improving the computation of contact mechanics when many contact points are involved, by aggregating the multiple contact constraints into a minimal set of constraints. We also introduce a method for non-uniform pressure distribution over the contact surface, to adapt the response when touching sharp edges. We use the Coulomb-Contensou friction model to efficiently simulate tangential and torsional friction. We show through different use cases that our aggregate constraint formulation is well-suited for simulating interactively dexterous manipulation of virtual objects through soft fingers, and efficiently reduces the computation time of constraint solving